Cybersecurity in Accounting Information Systems: Challenges and Solutions - Nurwanah, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the challenges and solutions in securing Accounting Information Systems (AIS) amidst increasing cybersecurity threats, emphasizing the integration of technological, human, and organizational factors. Research Design and Methodology: This study employs a qualitative approach, utilizing case studies and expert interviews across various sectors. The research framework draws on the Technology-Organization-Environment (TOE) and Socio-Technical Systems (STS) theories to provide a comprehensive analysis of AIS security dynamics. Findings and Discussion: The research highlights the growing sophistication of cyber threats, necessitating advanced technological solutions, including encryption, multi-factor authentication (MFA), and artificial intelligence (AI), for real-time threat detection and mitigation. Despite these advancements, human factors, such as insufficient cybersecurity awareness and organizational aspects, including inadequate security policies and investment, remain significant vulnerabilities. The study highlights the vital importance of a robust cybersecurity culture, effective governance, and regulatory compliance in enhancing AIS security. Implications: The findings underscore the importance of adopting a holistic approach to AIS cybersecurity, which combines technological advancements with robust organizational practices and ongoing training. Organizations are advised to foster a culture of cybersecurity awareness, develop clear policies, and ensure top management support to enhance their cybersecurity posture. These insights offer actionable recommendations for organizations seeking to safeguard their AIS against evolving cyber threats.